Investment treaties and the replacement of stranded investment - Henrik Horn; Mark Sanctuary (Research Institute of Industrial Economics (IFN), 2024)
Halting the ongoing global loss of biodiversity will require extensive phase-out of harmful production. A significant share of the affected production will be foreign-owned, and can therefore potentially be covered by investment treaties. These treaties are sometimes alleged to dissuade host countries from phasing out harmful investments, while other observers argue that the treaties are needed to provide incentives for the replacement investments that are required to prevent large income losses. To examine the impact of investment treaties on biodiversity protection, this paper studies a setting with both a stranded and a replacement investment. Among other findings, the paper shows how the dissuading effect of the agreement on host country regulation of the replacement investment, induces the investor to choose a replacement investment that is harmful to biodiversity, and how this in turn reduces the host country's willingness to phase out the stranded investment. The framework also sheds light on fundamental legal notions such as investor "legitimate expectations," "full compensation," and "investment."
Keywords: F21; F23; F53; K33; 330; International investment agreement; Biodiversity protection; Regulatory chill; Legitimate expectations